Ações poéticas urbanas: processos e práticas coletivas, artísticas e pedagógicas - Nogueira, Emilliano Alves de Freitas (2022)
In this research, I propose a reflection about collective, artistic and pedagogical processes and practices, having as object of study the production carried out by the Urban Poetic Actions Collective (CAPU), made up by members of the academic community of the Federal University of Goiás - Goiás Campus. I will introduce investigations questioning the reading, apprehension and ways of intervening in the urban space from artistic practices, and the learning processes involved in it, considering the interrelation between art, visual culture, education and architecture and urbanism. The study of urban collective practices in this research intends to articulate art and politics, from these actions investigation and how the pedagogical practice takes place through the experience in art actions in urban space. With a qualitative character, I intend with this work to understand how artistic and educational processes are built, using a/r/tography as a research methodology in the practices of the Urban Poetic Actions Collective, questioning the roles played by me in this process, as an artist, a researcher, a professor and a CAPU member. In the context of Goiás City, six interventions created by the collective will be introduced, producing counter-visualities as questioners of the hegemonic narratives in the city, highlighting the potential of these actions in discussions about memory, heritage and city. From these actions, I will discuss the relations produced between the artistic making and the knowledge that is built from collective creation, covering the paths of conception, production, presentation, mediation and criticism.